(untitled) (mathematica didactica, 2010)
A central element of pedagogical approaches is that students recognize mathematical coherences on their own. The theoretical backgrounds of these processes of discovering are rather vague. Questions arise like: How is it possible that students acquire (mathematical) knowledge on their own? Resp.: What are the conditions for these processes? In this article, abduction is used to describe the processes and outcomes of discovering mathematical coherences by elaborating on their underlying rational structures. The theoretical considerations will be guided by a scene of classroom interaction.